Knowing you [large type] - Peterson, Tracie (Peterson, Tracie. Pictures of the heart, 2023)
"May Parker is captivated by the Japanese exhibits at the Alaska-Yukon-Pacific Exposition, longing to know more about her mother's heritage. When she's reunited with childhood friend Lee Munro, they become entangled in a dangerous heist involving samurai armor, and their love is threatened. Will they be able to overcome the odds against them?"--